59.6k views
3 votes
(10.05 MC) Simplify cos2 Θ(1 + tan2 Θ). (2 points)

User Meher
by
6.2k points

2 Answers

1 vote

Answer:

The simplified form of the expression is


\cos^2\theta(1+\tan^2\theta)=1

Explanation:

Given : Expression
\cos^2\theta(1+\tan^2\theta)

To find : The simplification of the expression?

Solution :

Step 1 - Write the expression


cos^2\theta(1+\tan^2\theta)

Step 2 - Using the trigonometric property,


\tan\theta = (\sin \theta)/(\cos\theta)

Substitute in place of
\tan\theta


=cos^2\theta(1+((\sin \theta)/(\cos\theta))^2)


=cos^2\theta(1+((\sin^2 \theta)/(\cos^2\theta)))

Step 3 - Taking LCM,


=cos^2\theta((\cos^2\theta+\sin^2 \theta)/(\cos^2\theta))


=cos^2\theta((1)/(\cos^2\theta))

Step 4 - Cancel the term


=1

Therefore, The simplified form of the expression is


\cos^2\theta(1+\tan^2\theta)=1

User StevenZ
by
6.1k points
4 votes
Since tanΘ = sinΘ / cosΘ:
cos^2 Θ (1 + tan^2 Θ)
= cos^2
Θ (1 + sin^2 Θ / cos^2 Θ)
Distributing:
= cos^2
Θ + sin^2 Θ
By the Pythagorean identity,
= 1
User Seth Reno
by
6.2k points